2022
DOI: 10.1186/s12879-021-06993-w
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study assessing the clinical outcomes and costs of acute hepatitis A in Cape Town, South Africa

Abstract: Background While some evidence has been demonstrated the cost-effectiveness of routine hepatitis A vaccination in middle-income countries, the evidence is still limited in other settings including in South Africa. Given this, the evidence base around the cost of care for hepatitis A needs to be developed towards considerations of introducing hepatitis A vaccines in the national immunisation schedule and guidelines. Objectives To describe the severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Our 13 Further to the high cost and morbidity/mortality, Bruckmann et al showed that HAV is currently the leading cause of paediatric acute liver failure requiring transplantation in South Africa, with even further expenses and disease burden to the health sector. 14 The study was limited by participant enrolment in a single urban centre.…”
Section: Discussionmentioning
confidence: 69%
“…Our 13 Further to the high cost and morbidity/mortality, Bruckmann et al showed that HAV is currently the leading cause of paediatric acute liver failure requiring transplantation in South Africa, with even further expenses and disease burden to the health sector. 14 The study was limited by participant enrolment in a single urban centre.…”
Section: Discussionmentioning
confidence: 69%
“…Patterson et al reviewed patients presenting with hepatitis A at tertiary level hospitals Cape Town, South Africa, and calculated the total cost per hepatitis A hospitalization of $1935.41 for adult patients and $563.06 for pediatric patients. Furthermore, more www.nature.com/scientificreports/ than 1 in every 10 hepatitis A cases (13.3%) developed complicated hepatitis A or resulted in death 13 . Further to the high cost and morbidity/mortality, Bruckmann et al showed that HAV is currently the leading cause of pediatric acute liver failure requiring transplantation in South Africa, with even further expenses and disease burden to the health sector 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The cost inputs displayed in Table 3 for hepatitis A outpatient and inpatient treatment at tertiary healthcare facilities were taken from Patterson et al 2022 [ 21 ]. The cost of liver transplant was broken down into treatment of transplant cases and cost of transplant procedures at tertiary healthcare facilities.…”
Section: Methodsmentioning
confidence: 99%